A survey on factors which positively influence ethical decision making among young lawyers practising in the state of Kedah / Haswira Nor Mohamad Hashim ...[et al.] - Mohamad Hashim, Haswira Nor; Mahmood, Anida; Mansor, Kamarul Ariffin (2007)
This study focus on the issues concerning ethical decision making among the young lawyers practicing in the state of Kedah. The central aim of this study is to determine what factors positively influence ethical decision making among the young lawyers in Kedah, the degree of influence and whether there is any difference between gender, race and religion in terms of ethical decision making. Data were collected from 133 young lawyers who are practicing in the state of Kedah between January - June 2006 through self-administered and close-end questionnaires. Based on the mean score analysis the result shows that professional attributes (commitment, job satisfaction, salary, experience, motivation), personal values (religious value, moral value, family value) and law (imprisonment, fine, suspension, struck- off the rolls) are three major factors which highly contribute to the ethical decision making among young lawyers in Kedah. This is followed by three other factors : social environment (culture, tradition, peer), business environment (firm’s policy, competition, opportunity, profit, pressure) and knowledge (pupilage, ethics course, law degree). At the end of this research paper, several recommendations have been made in order to improve the ethical decision making of the young lawyers especially in the state of Kedah.